2020
DOI: 10.1002/rcm.8712
|View full text |Cite|
|
Sign up to set email alerts
|

Calibrating temperature reconstructions from fish otolith oxygen isotope analysis for California's critically endangered Delta smelt

Abstract: The surname of the sixth author of Willmes et al 1 was incorrectly spelled in the original published article as "Christian Denny". The correct name is "Christian Denney".

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…The surname of the sixth author of Willmes et al was incorrectly spelled in the original published article as “Christian Denny”. The correct name is “Christian Denney”.…”
mentioning
confidence: 99%
“…The surname of the sixth author of Willmes et al was incorrectly spelled in the original published article as “Christian Denny”. The correct name is “Christian Denney”.…”
mentioning
confidence: 99%
“…Since previous studies have indicated the depositional settings to be shallow marine proximal to the coast (Narayanan et al., 2007; Raha et al., 1983), the paleo‐environmental water composition was determined assuming a brackish habitat (1,000 ln α = 18.39 (10 3 TK −1 ) – 34.56) by Willmes et al. (2019). The effect of the choice of fractionation factor on the final reconstructed δ 18 O‐water is discussed in Text S4 in Supporting Information .…”
Section: Methodsmentioning
confidence: 99%
“…However, most of the vaterite observed in cultured delta smelt was present only on rostral, www.nature.com/scientificreports/ ventral, and postrostral lobes of the otolith, with the dorsal lobe remaining mostly free of any vaterite. Thus, results from studies that utilize the dorsal lobe of delta smelt otoliths are likely less susceptible to variation in otolith minerology 33,35,44,51 . The quantification of such patterns is key to developing robust methods in otolith research 8,32 .…”
Section: Consequences Of Otolith Abnormalitiesmentioning
confidence: 99%
“…For example, little is known about the comparative health and survival of cultured versus wild individuals, and such differences could influence the outcomes of experiments and supplementation efforts using cultured fish. Similarly, otolith-based analyses have been used to describe environmental effects on growth 33 and life history 35,43,44 of wild delta smelt; however, the prevalence and potential effects of crystalline anomalies have not been examined. Studies that quantify developmental abnormalities in otoliths, therefore, are important for examining differences in health and fitness among wild and cultured fish populations and for validating the interpretation of otolith-based metrics.…”
mentioning
confidence: 99%